Romania and the Crisis in the Health System. Migration of Doctors (Global Journal of Medical Research, 2013)
Migration of doctors in Romania still continues today producing a range of long-term social, economic and demographic effects. Current data on the migration of these specialists from our country shows a negative trend, therefore according to the figures offered by the College of Physicians in Romania, only since 2007 10,000 doctors have chosen to work in the West, and 400 submit applications monthly to the Ministry of Health. This paper brings to the attention issues related to the scale of the Romanian medical migration. For this purpose, we used different statistical data provided by specialized institutions in the country and abroad, information provided by the media, the results of studies published in the field. The goal is a better understanding of the dimensions of the phenomenon, for which the analysis is completed by means of the interactionist and interpretative method according the constructivist perspective. The results obtained in this study consist of the discolure of certain current issues followed by the presentation of social effects and social, economic and demographic dimensions of the Romanian medical system from the perspective of medical migration
Keywords: medical migration; brain drain; sanitation system; human resources; performance